Peran Penyuluhan Pertanian Terhadap Pengendalian Hama Terpadu pada Tanaman Padi Berdasarkan Kelas Kemampuan Kelompok Tani di Kecamatan Labuan Amas Selatan Kabupaten Hulu Sungai Tengah - Risna Risna; Masyhudah Rosni; Mariani Mariani (AGRIDES: Jurnal Agribisnis Perdesaan, 2012)
The study is purposed to know the role of agricultural extension and its difference on rice integrated pest control base on farmer group’s capability level. The study was conducted in Kecamatan Labuan Emas Selatan on Maret – Juni 2012. The variable considered was the role of agricultural extension which consists of: education, dissemination, facility, consultation, supervision, monitoring and evaluation. The respondents were selected through multiple stages random sampling as follows. First, 5 extensioner working areas (WKPs) were purposive selected. Then, two farmer groups – initial and advanced group, were selected from each WKP. From each groups, 2 committee members were taken as respondent, so total respondents were accounted 40 people. The result shows that the role of agricultural extension on integrated pest control is categorized as low level in initial farmer group (score 54.46%), while in advanced group is categorized as medium level (score 64.70%). The extension does not cover all roles as certain role, i.e.: supervision, monitoring and evaluation, are not conducted properly. There is difference extension role based on farmer group capability level.